2005
DOI: 10.1016/j.molcel.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Transcription and Heterochromatin at the DM1 CTG Repeats Are Constrained by CTCF

Abstract: Prior studies of the DM1 locus have shown that the CTG repeats are a component of a CTCF-dependent insulator element and that repeat expansion results in conversion of the region to heterochromatin. We now show that the DM1 insulator is maintained in a local heterochromatin context: an antisense transcript emanating from the adjacent SIX5 regulatory region extends into the insulator element and is converted into 21 nucleotide (nt) fragments with associated regional histone H3 lysine 9 (H3-K9) methylation and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
290
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(306 citation statements)
references
References 23 publications
15
290
1
Order By: Relevance
“…Although in most repeat expansion diseases, the sense strand transcript or its translated protein products are thought to have primacy in disease pathogenesis, discovery of antisense strand transcripts is leading to increasing appreciation of their potential significance in disease pathogenesis (45)(46)(47)(48)(49)(50)(51)56). In FXTAS, antisense strand transcripts, as well as sense strand transcripts, are up-regulated, polyadenylated at the 3′ end, and capped at the 5′ end (47), although only the sense strand is known to generate nuclear inclusions (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in most repeat expansion diseases, the sense strand transcript or its translated protein products are thought to have primacy in disease pathogenesis, discovery of antisense strand transcripts is leading to increasing appreciation of their potential significance in disease pathogenesis (45)(46)(47)(48)(49)(50)(51)56). In FXTAS, antisense strand transcripts, as well as sense strand transcripts, are up-regulated, polyadenylated at the 3′ end, and capped at the 5′ end (47), although only the sense strand is known to generate nuclear inclusions (57).…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that in several other examples of expanded nucleotide repeat diseases, bidirectional transcription of the repeat has been identified (45)(46)(47)(48)(49)(50)(51), and that a recent study reported antisense transcripts in C9orf72 patient nervous systems (20), we examined C9orf72 patient fibroblasts for accumulation of RNAs transcribed in the antisense direction. Using FISH with LNA probes to the antisense strand of the hexanucleotide repeat GGCCCC, RNA foci were identified in all six fibroblasts from C9orf72 expansion patients tested and were not observed in fibroblasts from three nonaffected individuals (Fig.…”
Section: Antisense Strand Of C9orf72 Is Transcribed and Ggcccc Expanmentioning
confidence: 99%
“…The DM1 alleles under study are identical except in sequences at the CTCF-binding sites that contain base substitutions to eliminate CTCF binding (ref. 20; Fig. S5).…”
Section: Detection Of Ctcf Interacting Proteins By Isotope Coded Affimentioning
confidence: 99%
“…To test whether the association of Scc3/SA1 with chromatin directly depended on the presence of CTCF, we analyzed Scc3/SA1 binding at both a normal and a mutated CTCF-dependent insulator element of the human myotonic dystrophy gene DM1 that had been integrated at the same genomic locus in mouse 3T3 cells via recombination-mediated cassette exchange (RMCE; ref. 20). The DM1 alleles under study are identical except in sequences at the CTCF-binding sites that contain base substitutions to eliminate CTCF binding (ref.…”
Section: Detection Of Ctcf Interacting Proteins By Isotope Coded Affimentioning
confidence: 99%
“…For instance, microdeletion or microduplications of the CTCF sites at the IGF2/H19 locus are associated with some cases of non syndromic Wilm tumors. 49 Also, CTCF flanks CTG/CAG trinucleotide repeats at several disease-associated loci, such as the DM1 locus implicated in myotonic dystrophy, an autosomal dominant multisystemic disorder characterized by myotonia, muscular dystrophy, cataracts, hypogonadism, cardiac conduction anomaly and diabetes mellitus, 50,51 which is caused by a CTG repeat expansion. The physiopathology of DM1 is not fully elicited and may be linked to a complex mechanism involving chromatin changes and CTCF.…”
Section: Is the Molecular Mechanism Of Fshd Relevant For Other Patholmentioning
confidence: 99%